Front Cover: Coupling of Silk Fibroin Nanofibrils Enzymatic Membrane with Ultra‐Thin PtNPs/Graphene Film to Acquire Long and Stable On‐Skin Sweat Glucose and Lactate Sensing (Small Methods 3/2021). Issue 3 (15th March 2021) - Liu, Xiaotian; Zhang, Wenli; Lin, Zaifu; Meng, Zhaohui; Shi, Chenyang; Xu, Zhijun; Yang, Likun; Liu, Xiang Yang
Abstract : In article number 2000926 by Likun Yang, Xiang Yang Liu, and co‐workers, 3D functional scaffolds of porous enzymatic nanofibers (PEN) effectively retain enzymes and provide large surface areas for molecular/ion diffusion and biochemical reactions. The PEN membrane further attaches to the Pt‐G nanocomposite film to facilitate the electron transport, which permits highly effective glucose and lactate sensing with long and stable performance.